Crop varieties, phenological phases and the yield-weather relationship: evidence from the Italian durum wheat production - Marco Tappi; Federica Carucci; Anna Gagliardi; Giuseppe Gatta; Marcella Michela Giuliani; Fabio Gaetano Santeramo (Bio-based and Applied Economics, 2023)
The impacts of extreme weather events on crop productions are largely heterogeneous along the timing dimension of the shocks, and the varieties being affected. We investigate the relationships yield-weather for three durum wheat varieties (early, middle, and late). We disentangle the time dimension distinguishing five phenological stages, as identified by Growing Degree Days approach. Our panel regression models show that the starting and development stages are sensitive to changes in minimum temperatures, regardless of wheat variety. Raises in maximum temperatures during the starting stage are associated with increases in yields; the opposite is true for increases in high temperatures from seed fill to dough stage (for late varieties), and at maturity complete stage (for early varieties). The analysis suggests that advancing sowing dates may help preventing yield losses due to heat stress, whereas the cold stress should be managed through other on-farm risk management strategies or via crop insurance.